A retrospective cohort study of hemostatic agent use during hysterectomy and risk of post‐operative complications. Issue 2 (16th November 2016) - Harris, John A.; Uppal, Shitanshu; Kamdar, Neil; Swenson, Carolyn W.; Campbell, Darrell; Morgan, Daniel M.
Abstract: Objective: To determine if the use of intraoperative hemostatic agents was a risk factor for post‐operative adverse events within 30 days of patients undergoing hysterectomy. Method: A population‐based retrospective cohort study included data from patients undergoing hysterectomy for any indication between January 1, 2013, and December 31, 2014, at 52 hospitals in Michigan, USA. Any individuals with missing covariate data were excluded, and multivariable logistic regression and propensity score‐matching were used to estimate the rate of post‐operative adverse events associated with intra‐operative hemostatic agents independent of demographic and surgical factors. Results: There were 17 960 surgical procedures included in the analysis, with 4659 (25.9%) that included the use of hemostatic agents. Hemostatic agent use was associated with an increase in predicted hospital re‐admissions ( P =0.007). Among all hysterectomy approaches, and after adjusting for demographic and surgical factors, hemostatic agent use during robotic‐assisted laparoscopic hysterectomy was associated with an increased predicted rate of blood transfusions ( P =0.019), an increased predicted rate of pelvic abscess diagnoses ( P =0.001), an increased predicted rate of hospital re‐admission ( P =0.001), and an increased predicted rate of re‐operation ( P =0.021). Conclusion: Hemostatic agents should be used carefully owing to associations with increased post‐operative re‐admissions and re‐operations when used during hysterectomy. Abstract : Among women in Michigan, USA, the use of hemostatic agents during hysterectomy was associated with an increased rate of post‐operative complications.